2020
DOI: 10.56093/ijas.v90i11.108583
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of cucumber (Cucumis sativus) accessions differing in quantitative traits and microsatellite markers

Abstract: The genetic diversity among 78 cucumber (Cucumis sativus L.) accessions was analyzed using 8 morphological traits and 60 SSR markers under two environmental (open field and protected cultivation) conditions. D2 analysis had grouped the 78 accessions in five major clusters. Cluster I comprised 51 accessions followed by 14, 5, 7 and 1 in cluster II, III, IV, and V respectively. The variation was observed for morphological characters like days to first female flower anthesis (37.53-58.64), days to first fruit har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…However, the PIC value ranged from 0.06 to 0.81 (mean 0.38); slightly higher than the PIC value (3.69) reported by [31] and 0.17 reported by [37], and lower than the PIC value (4.29) reported by [19]. The presence of a slightly high level of PIC in 96 bitter gourd genotypes of the present study might be due to high cross-pollination behaviour and similar findings were reported in other cross-pollinated crops such as cucumber [38,39].…”
Section: Discussionsupporting
confidence: 64%
“…However, the PIC value ranged from 0.06 to 0.81 (mean 0.38); slightly higher than the PIC value (3.69) reported by [31] and 0.17 reported by [37], and lower than the PIC value (4.29) reported by [19]. The presence of a slightly high level of PIC in 96 bitter gourd genotypes of the present study might be due to high cross-pollination behaviour and similar findings were reported in other cross-pollinated crops such as cucumber [38,39].…”
Section: Discussionsupporting
confidence: 64%
“…reported similar results for fruit diameter (4.16 to 6.82 cm). Signi cant variations were observed for individual fruit weight among genotypes and it ranged from 130.33 g − 334 g Kumar et al (2020). have reported similar results in cucumber accessions (124.63 g − 417.55 g).…”
mentioning
confidence: 52%